Entropie im System - die strukturelle Beschaffenheit der betrieblichen Kraftbasis - Hans-Christian Krcal (University of Heidelberg, Department of Economics, 2020)
– Within firms diverse fields of action are regarding the transformation of material and immaterial resources. The dimension of choices is being determined by the basic laws of thermodynamics. The entropic relevance of action within a firm has been considered by the paper. From a social system theory perspective the impact of energy flow and its qualities on the decisional opportunity level is being discussed. It can be shown that from the perspective of thermodynamics the threat by equilibrium has some essential consequences for the firm's decision making in general.
urn:nbn:de:bsz:16-heidok-289411
Keywords: B49; D24; D29; B41; M10; M20; P18; Q43; 330; closed and open system; thermodynamics; decision making; entropy; steady state and thermodynamic equilibrium